2021
DOI: 10.1590/s1679-4974202100017.esp1
|View full text |Cite
|
Sign up to set email alerts
|

Protocolo Brasileiro para Infecções Sexualmente Transmissíveis 2020: infecção pelo vírus Zika

Abstract: Resumo Este artigo aborda as transmissões vetorial, sexual e vertical do vírus Zika, tema contemplado no Protocolo Clínico e Diretrizes Terapêuticas para Atenção Integral às Pessoas com Infecções Sexualmente Transmissíveis, publicado pelo Ministério da Saúde do Brasil em 2020. Embora no Brasil o vírus Zika seja predominantemente veiculado pelo Aedes aegypti, as vias vertical e sexual de transmissão apresentam expressiva importância para a saúde reprodutiva. A transmissão sexual demanda o uso de intervenções pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 59 publications
(75 reference statements)
0
5
0
2
Order By: Relevance
“…Este virus tiene la capacidad de aislarse en el líquido amniótico, membranas fetales, placenta y tejido cerebral fetal. 24,25,26 Método de Diagnóstico El diagnóstico del Zika es realizado por confirmación laboratorial, visto que, la literatura afirma que no hay un factor clínico, bioquímico o radiológico patognomónico de la infección 16,20 . De acuerdo con los autores el examen estándar de oro es el aislamiento del virus en un cultivo viral, por el contrario, esta forma de detectar la infección presenta baja sensibilidad.…”
Section: Resultados Y Discusiónunclassified
“…Este virus tiene la capacidad de aislarse en el líquido amniótico, membranas fetales, placenta y tejido cerebral fetal. 24,25,26 Método de Diagnóstico El diagnóstico del Zika es realizado por confirmación laboratorial, visto que, la literatura afirma que no hay un factor clínico, bioquímico o radiológico patognomónico de la infección 16,20 . De acuerdo con los autores el examen estándar de oro es el aislamiento del virus en un cultivo viral, por el contrario, esta forma de detectar la infección presenta baja sensibilidad.…”
Section: Resultados Y Discusiónunclassified
“…( 3 , 61 ) Through anamnesis, the health professional must be aware of symptomatic pregnant and puerperal women returning from these areas (less than 14 days). ( 62 ) Likewise, consider the possible coincidence of epidemiological scenarios where the frequency of measles, Covid-19 and leptospirosis cannot be ruled out. ( 21 , 63 )…”
Section: Epidemiological Variablesmentioning
confidence: 99%
“…In several parts of the country, these samples still need to be sent to centralized official laboratories, which delays the diagnostic process. ( 62 ) Some assays can diagnose dengue, zika and chikungunya in a single sample. The suggestion is, before obtaining the sample, checking the forwarding flow to the laboratory in which it will be processed.…”
Section: Epidemiological Variablesmentioning
confidence: 99%
“…One of the latest reports described new cases of active vector transmission of ZIKV in France ( 7 , 8 ). Although the overall number of ZIKV infections is now declining; e.g., in 2020 in Brazil, there were over 3,500 confirmed cases versus 215,000 in 2016, ZIKV is still actively circulating in Latin America and Asia ( 9 ). Recent studies have shown new ZIKV African strains have emerged in mosquitoes and primates, and these strains are genetically different from pandemic strains by 15%; in addition, these strains are more infectious and pathogenic to fetuses ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%